PENGARUH SENAM JANTUNG SEHAT TERHADAP TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI - Arisandi " "; Bayhakki " "; Riri " Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract   This study aimed to determine the effect of a healthy heart gymnastic exercises on blood pressure in the elderly with hypertension. This study used quasy experiment research design with non-equivalent control group. The study was conducted in PSTW Khusnul khotimah. The samples used were 32 people which taken is simple random sampling technique and met the inclusion criteria. The experimental group was given therapeutic intervention healthy heart gymnastic 6 times for 2 weeks. The measuring instrument used was a mercury sphygmomanometer and observation sheet. The analysis used was bivariate analysis with dependent t test and independent t test. The results showed that the average diastole blood pressure in the experimental group before being given intervention 157.37 mmHg, while the average blood pressure of 146.69 mmHg after intervention by the p value of 0.000 then the p value <α (0.05). It means there is a difference in blood pressure after given intervention in experimental group. The results showed that a healthy heart gymnastic therapy effectively lower blood pressure in patients with hypertension and can be used as a nursing intervention in helping to lower blood pressure in hypertensive patients. Keywords: hypertension, blood pressure, diastole, healthy heart gymnastic exercises